Палеоекономічна реконструкція суспільства степових мисливців - Залізняк, Л.Л. (Археологія, 1996)
Стаття присвячена типам господарства та способу життя мисливської людності степової та лісо-степової зон України у пізньому палеоліті та мезоліті. Виділяються історичні етапи розвитку економіки степових мисливських суспільств. В каждой природно-ландшафтной зоне первобытное общество вырабатывало своеобразный образ жизни, модель экономической адаптации или хозяйственно-культурный тип. Модель хозяйственной адаптации степных охотников окончательно сложилась в Северном Причерноморье в середине позднего палеолита.
В степях Украины прослеживается три стадии развития данной модели. С момента формирования до финального палеолита (20000—13000 лет тому назад) она развивалася в форме специализированных степных охотников на бизонов. В финальном палеолите (13000—10000 лет назад) степные охотники перешли к промыслу лошади.
Около 10000 лет назад холодные причерноморские степи приледниковья трансформировались в раннеголоценовые с более мягким и влажным климатом и большей ролью лесных биоценозов, включающих представителей лесостепной фауны (тур, кабан, благородный олень). Хозяйственно-культурный тип степных охотников перешел с перигляциального на раннеголоценовый, мезолитический этап развития.
В Северном Причерноморье степная модель охотничьей адаптации просуществовала до неолита, а североамериканских прериях вплоть до XIX в. The existence of landscape-climatic, zones in Europe was responsible for a hunting specialization of the population and a certain cultural differentiation of the inhabitants in each of the zones. At the end of the Paleolithic and the Mesolithic periods seven models of economy adaptation or economic-cultural types were formed in there. They were the following: mammoth hunters, reindeer hunters, mounting periglacial hunters, forest hunters, mountain forest hunters, hunters and fishers of the river banks, and steppe hunters.
The model of economy adaptation of the steppe hunters had been formed in the Ukrainian Steppe in the glacial maximum, about 20000 years ago (Amvrosiivka, Anetovka II). This type of prehistoric economy spread out to the East of the steppe zone and in the end of the Paleolith reached the Siberian Steppe. On the border of the Pleistocene and the Holocene, it spread out in the American Prairies.
The steppe model of a hunting economy had three development stages in the Ukrainian steppes. From the moment of formation up to the Final Paleolith (20 000 - 13 000 years ago), it existed in the form of specialized bison hunters. In the Final Paleolith (13 000-10 000 years ago) it transformed into the economy of horse hunters.
About 10 000 years ago the cold periglacial Pontic steppes were changed for the Early Holocene steppes with more mild climate, more developed forest impregnation, where the Pleistocene bison and horses were superseded by aurochs, tarpans and saigas. Thus, at the verge of the Pleistocene and the Holocene the transition of the Late Paleolithic model of a steppe economy to the Early Holocene stage of its development was defined in the Pontic steppes.
In the Northern Pontic Areas, the steppe-hunters’ adaptation model existed till the Neolith. In the prairies of Northern America, it was up to the 19 century. This makes it possible to reconstruct the mode of life of the Final Paleolithic and Mesolithic hunters in the Northern Pontic Areas not only on the basis of archaeological data, but also using ethnographic ones.